Racial Attitudes in the United States as Perceived From the Outside - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
America, the melting pot, embraces many non-white citizens as well like Blacks, Indians, Asiatic people and Hispanics. The history of the nation includes bitter struggles for equality especially for Blacks, the major racial minority. With time great leaps in abolishment of segregation and later in reduction of discrimination were achieved. Ideally still many problems may wait to be solved. But under realistic circumstances, today's overall situation represents an admirable understanding of and the establishment of a good social skill in living in harmony and peace all together. (C) 2015 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license.
Keywords: America; race; ethnicity; prejudice; discrimination; attitude